Juggler of worlds - Niven, Larry (Tor, 2008)
Two hundred years before the discovery of the Ringworld, covert agent Sigmund Ausfaller represents Earth's secret weapon, humanity's best defense against all conspiracies--real and imagined. Who better than a brilliant paranoid to expose the devious plots of others? Yet he may finally have met his match in Nessus, representative of the secretive Puppeteers, the elder race who wield vastly superior technologies. Nessus schemes in the shadows with Earth's traitors and adversaries, even after the race he represents abruptly vanishes from Known Space.